(3GdcdjGJ aj GdWHs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdZQV aj gPG Gdbhd Cf JKHJ gGgfG ef UfGYI GdWH LedI cGajI Ef UfGYI GdWH gj UfGYI aGYdI Yf eHGOF UGObI adJeS HgG MaX UMI HOf GdEfSGf s
(3BNQgG (B:s
(3hEYUGA GdCSHGH Ydi YGOI CUMGH GdcfGFT , hdG MGLI def s
(3GdfSNI HgG MhGTs
(3YdjgG Jedc deMeO Hf eMeO GdbhUhfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B313s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3eJaQbGJs